Recent Trends in the Development of Jewish Life and Heritage Tourism in Trani, Italy - Andrea Corsale (International Journal of Religious Tourism and Pilgrimage)
This paper focuses on the recent revival of Jewish religious and cultural activities in the coastal town of Trani, in Southern Italy, after several centuries of substantial interruption. The specific events which led to the re-establishment of an institutional Jewish community and the restoration and reclamation of the local synagogues, along with the renewed visibility of the well-preserved Jewish district, of Medieval origins, are unique to this case study. However, at the same time, they reflect similar phenomena of restoration of Jewish sites and revival of Jewish communities in southern and eastern Europe, and beyond. As the case study analysis shows, Jewish-themed tourism has been growing as a consequence of this religious comeback, and it works as a stimulus and magnet for public projects and private investments aimed at further developing (or even capitalising on) this trend, for various purposes. The management of heritage and cultural tourism is closely connected to the complex identity of religious minority groups, where different components tend to produce different visions and practices. Actors, discourses, and reasons behind the management and promotion of Jewish culture will be highlighted and the representations and visions of the various stakeholders and groups involved will be portrayed, with the aim of contributing to the discussion about the complexity of managing minority heritage in tourist destinations.